GENERATION Z PURCHASE DECISION ON TIK-TOK SHOP IN TASIKMALAYA CITY: ANALYSIS OF INNOVATION, QUALITIES, PROMOTION AND E-TRUST - Awaluddin, Robi; Aliyuddin, Muhammad; Hendratawan, Febrialdy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to analyse consumer behaviour regarding purchasing decisions in Tik-Tok's live shopping based on Product Innovation, Product Quality, Promotion, and e-Trust. Furthermore, this research is a quantitative research involving stratified random sampling consisting of 202 Generation Z respondents that live in the city of Tasikmalaya, the spreading of set of questionnaires is using direct filling Google form to reduce the use of paper. Data analysis technique using Multiple Linear Regression Analysis by SPSS Version 26. Result from this research is that Product Innovation, Product Quality, Promotion and e-trust in both partially and simultaneously have a positive and significant impact to consumer purchase decisions in Z generation located in Tasikmalaya, Indonesia. The novelty of this research is examines the impact on consumer decision buying decision in Tik-Tok social commerce in Indonesia which is a new model as a type of e-commerce